Factors associated with students’ performance in G.C.E (O/L) examination: A case of Northern Province of Sri Lanka - Nithlavarnan, A. (University of Colombo, Sri Lanka, 2018)
Students’ academic performance is a key feature in Education. Many factors influence students' performance in the G.C.E (O/L) examination. The Northern Province of Sri Lanka is severely affected by the long term civil war. Due to the war and post-war effects, fluctuations are found in students' performance in G.C.E (O/L) examination. The decreasing the students’ performance will have a massive impact on the sustainable development of Northern Province. It may lead to a decrease in intellectual capacity. This study investigates students' performance and the elements that influence it in the G.C.E (O/L) examination in Sri Lanka's Northern Province. It used a mixed method approach to address the research issue since it was influenced by a three-phase pragmatism research philosophy. The case study included twenty-one schools from eight different educational zones. Primary data was gathered from school principals, teachers, students, ZDEs, ADEs, and ISAs utilizing KII and FGD. Secondary data obtained from the Department of Examination and Education Management Information System. The study found that during the war era (before 2009), the Northern Province had a greater percentage of students passing the G.C.E (O/L) test than the rest of the country, but this was reversed in the post-war era. It was also discovered that the percentages of students who passed the G.C.E (O/L) examination in the Northern Province from 2005 to 2019 was inconsistent across time and location. It was also discovered that students, teachers, school resources, examinations, curriculum, family, and society all had an impact on students' performance.
Keywords: Students; Performance; G.C.E (O/L); Northern